Willingness to pay for methadone maintenance treatment in Vietnamese epicentres of injection-drug-driven HIV infection - Bach Xuan Tran (The World Health Organization, 2013)
OBJECTIVE: Willingness to pay for methadone maintenance treatment (MMT) in three Vietnamese epicentres of injection-drug-driven human immunodeficiency virus (HIV) infection was assessed. METHODS: A convenience sample of 1016 patients receiving HIV treatment in seven clinics was enrolled during 2012. Contingent valuation was used to assess willingness to pay. Interviewers reviewed adverse consequences of injection drug use and the benefits of MMT. Interviewers then described the government's plan to scale up MMT and the financial barriers to scale-up. Willingness to pay was assessed using double-bounded binary questions and a follow-up open-ended question. Point and interval data models were used to estimate maximum willingness to pay. FINDINGS: A total of 548 non-drug-users and 468 injection drug users were enrolled; 988 were willing to pay for MMT. Monthly mean willingness to pay among non-drug-users, 347 drug users not receiving MMT and 121 drug users receiving MMT was 10.7 United States dollars [US$] (35.7% of treatment costs), US$ 21.1 (70.3%) and US$ 26.2 (87.3%), respectively (mean: US$ 15.9; 95% confidence interval, CI: 13.6-18.1). Fifty per cent of drug users were willing to pay 50% of MMT costs. Residence in households with low monthly per capita income and poor health status predicted willingness to pay less among drug users; educational level, employment status, health status and current antiretroviral therapy receipt predicted willingness to pay less among non-drug-users. CONCLUSION: Willingness to pay for MMT was very high, supporting implementation of a co-payment programme.